Implementasi Role-Based Access Control (RBAC) pada Sistem Monitoring Kenaikan Jabatan Fungsional Guru - Muhammad Rivaldi; Triase Triase (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
As educators, functional position promotion (JaFung) serves as a means of advancing teachers’ careers as well as an indicator of their success in meeting established quality standards. However, in practice, this process still faces several challenges, such as teachers having difficulty monitoring the progress of their submitted proposals and institutions needing to contact teachers individually when issues arise. These problems indicate the absence of integration between progress monitoring and communication within a unified system. This study aims to propose a system model that integrates monitoring, communication, and RBAC-based security mechanisms. The Role-Based Access Control (RBAC) mechanism is used as a framework for managing interactions among actors across institutions and is designed using a scenario-driven role engineering approach to produce an RBAC model that adheres to the principle of least privilege. The system development method employed in this study is the Software Development Life Cycle (SDLC) using the Waterfall model. The results of black-box testing show that the developed system operates in accordance with its specifications and fulfills functional requirements. Access violation testing involving 10 unauthorized access attempts resulted in a violation rate of 0%, indicating that all unauthorized access was successfully prevented by the system. In addition, there was a 37.21% reduction in the number of permissions in the RBAC-implemented system, demonstrating the application of the least privilege principle. The proposed system not only facilitates document management and proposal progress monitoring but also enhances security and ensures more structured access management in the functional position promotion process.